Metabolic alterations accompanying oncogene-induced senescence - Aird, Katherine M (Mol Cell Oncol, 2014)
Senescence is defined as a stable cell growth arrest. Oncogene-induced senescence (OIS) occurs in normal primary human cells after activation of an oncogene in the absence of other cooperating oncogenic stimuli. OIS is therefore considered a bona fide tumor suppression mechanism in vivo. Indeed, overcoming OIS-associated stable cell growth arrest can lead to tumorigenesis. Although cells that have undergone OIS do not replicate their DNA, they remain metabolically active. A number of recent studies report significant changes in cellular metabolism during OIS, including alterations in nucleotide, glucose, and mitochondrial metabolism and autophagy. These alterations may be necessary for stable senescence-associated cell growth arrest, and overcoming these shifts in metabolism may lead to tumorigenesis. This review highlights what is currently known about alterations in cellular metabolism during OIS and the implication of OIS-associated metabolic changes in cellular transformation and the development of cancer therapeutic strategies.